Optimization design and performance evaluation of a novel asphalt rejuvenator - Yi, Jiao; Yuanguang, Xie; Zhengjia, Liu (Frontiers in Materials, 2022)
The development of regeneration agent is one of the key technologies for pavement regeneration and one of the methods to reduce carbon emission in transportation field, so it is very necessary to develop regeneration agent. Based on the composition of asphalt andrejuvenator components, the optimal dosing of extraction oil, plasticizer DOP and hydrogenated C9 petroleum resin was determined by response surface method, and the suitable dosing of anti-aging agent was also designed to optimize the orthogonal experiment to prepare ZJ-I rejuvenator with good overall performance. On the basis of ZJ-I rejuvenator, dynamic shear, bending creep stiffness, atomic force microscopy, Fourier infrared spectroscopy and contact angle experiments were used to investigate the effects of ZJ-Irejuvenator dosing on the high and low temperature rheology, chemical structure, surface microscopic morphology and adhesion between asphalt and aggregate of aged asphalt, and to explore the regeneration effect and regeneration mechanism of ZJ-I rejuvenator. The results showed that ZJ-I rejuvenator formulated with 83.6% extracted oil, 15% plasticizer DOP, 1.4% hydrogenated petroleum resin, 0.6% antioxidant and 0.4% light stabilizer has the best regeneration effect, and its optimal dosing is 7%. aging degree. It can also improve the adhesion performance of asphalt and aggregate.